Industrial manufacturing and characterization of multiscale CFRP laminates made from prepregs containing graphene-related materials - Verónica Rodríguez-García; Julio Gómez; Francesco Cristiano; María R Gude (Materials Research Express, 2020)
The introduction of graphene-related materials (GRMs) in carbon fibre-reinforced polymers (CFRP) has been proved to enhance their mechanical and electrical properties. However, methodologies to produce the 3-phase materials (multiscale composites) at an industrial scale and in an efficient manner are still lacking. In this paper, multiscale CFRP composites containing different GRMs have been manufactured following standard procedures currently used in the aerospace industry with the aim to evaluate its potential application. Graphite nanoplateletelets (GNPs), in situ exfoliated graphene oxide (GO) and reduced graphene oxide (rGO) have been dispersed into an epoxy resin to subsequently impregnate aeronautical grade carbon fibre tape. The resulting prepregs have been used for manufacturing laminates by hand lay-up and autoclave curing at 180 °C. A broad characterization campaign has been carried out to understand the behaviour of the different multiscale laminates manufactured. The degree of cure, glass transition temperature and degradation temperature have been evaluated by thermal evolution techniques. Similarly, their mechanical properties (tensile, flexural, in-plane shear, interlaminar shear and mode I interlaminar fracture toughness) have been analysed together with their electrical conductivity. The manufacturing process resulted appropriated for producing three-phase laminates and their quality was as good as in conventional CFRPs. The addition of GO and rGO resulted in an enhancement of the in-plane shear properties and delamination resistance while the addition of GNP improved the electrical conductivity.